The effect of combination of black garlic and turmeric on laying sequence of Magelang duck infected with Salmonella enteritidis - Monica Sonia Indri Pradipta; Yosephine Laura Raynardia Esti Nugrahini; Kurnia Islamia; Budi Santoso; Rio Kayisa; Syaiful Iqbal; Maulana Tri Andhani; Rifka Triyanto; Ujan Satrio (Universitas Tidar, 2019)
The digestive tract is the main key to an animal's health which manifests livestock productivity. Healthy animals produce optimal livestock productivity. The purpose of this study was to determine egg production from a combination of turmeric and garlic against Salmonella enteritidis infection or commonly referred to as Salmonellosis disease. The method of preparing turmeric and garlic is done by giving heat treatment at a temperature of ± 70° C, then given by mashing. The results showed that after infection with Salmonella enteritidis, abnormal egg-laying occurred, namely eggs are very small than normal. The productivity of magelang ducks infected by Salmonella enteritidis and supplemented with black garlic and turmeric (P2) can pursue control treatment (P0) and treatment without infection plus black garlic and turmeric supplementation (P1). Whilst, egg weight from treatment P1 was heavier than P0 and P2 after infection. It can be concluded that the addition of black garlic and turmeric can improve both egg productivity and egg weight. The productivity of Magelang duck eggs infected by Salmonella enteritidis and added turmeric and black garlic can recover within 2.5 weeks after infection.Keywords: Duck of Magelang, Salmonella enteritidis, black garlic, turmeric The digestive tract is the main key to an animal's health which manifests livestock productivity. Healthy animals produce optimal livestock productivity. The purpose of this study was to determine egg production from a combination of turmeric and garlic against Salmonella enteritidis infection or commonly referred to as Salmonellosis disease. The method of preparing turmeric and garlic is done by giving heat treatment at a temperature of ± 70° C, then given by mashing. The results showed that after infection with Salmonella enteritidis, abnormal egg-laying occurred, namely eggs are very small than normal. The productivity of magelang ducks infected by Salmonella enteritidis and supplemented with black garlic and turmeric (P2) can pursue control treatment (P0) and treatment without infection plus black garlic and turmeric supplementation (P1). Whilst, egg weight from treatment P1 was heavier than P0 and P2 after infection. It can be concluded that the addition of black garlic and turmeric can improve both egg productivity and egg weight.The productivity of Magelang duck eggs infected by Salmonella enteritidis and added turmeric and black garlic can recover within 2.5 weeks after infection. Keywords: Duck of Magelang, Salmonella enteritidis, black garlic, turmeric